7(3-2n)-1=6-7n

Simple and best practice solution for 7(3-2n)-1=6-7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3-2n)-1=6-7n equation:


Simplifying
7(3 + -2n) + -1 = 6 + -7n
(3 * 7 + -2n * 7) + -1 = 6 + -7n
(21 + -14n) + -1 = 6 + -7n

Reorder the terms:
21 + -1 + -14n = 6 + -7n

Combine like terms: 21 + -1 = 20
20 + -14n = 6 + -7n

Solving
20 + -14n = 6 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
20 + -14n + 7n = 6 + -7n + 7n

Combine like terms: -14n + 7n = -7n
20 + -7n = 6 + -7n + 7n

Combine like terms: -7n + 7n = 0
20 + -7n = 6 + 0
20 + -7n = 6

Add '-20' to each side of the equation.
20 + -20 + -7n = 6 + -20

Combine like terms: 20 + -20 = 0
0 + -7n = 6 + -20
-7n = 6 + -20

Combine like terms: 6 + -20 = -14
-7n = -14

Divide each side by '-7'.
n = 2

Simplifying
n = 2

See similar equations:

| 52+(-7)= | | x^2-4x=-x+70 | | 5(3+x)-(8x+9)=-4 | | a(t)=12-4t | | -38+7= | | 10x+9=2x-7 | | 3x^4(1-x)=0 | | -3.2=-6.8 | | -16+-29= | | x^2+17=-10x+1 | | -2(4-3k)+8k= | | x^2-90=2x-10 | | -8(b-87)=-72 | | 4b+1-b=7 | | 5p+5-6=6p+3-30 | | -3x-8=-(2x+7) | | 3s+16=6+4s | | 3(5x+8)=-36 | | -40-5x+10x=45 | | x^2+18x+90=1 | | 3t+7=5t+9 | | 6x-91+12x=47 | | 30=18k | | -.33x-7=17 | | 16x^3(1-x)=0 | | 15(20x+1)-10x=115 | | r^2-r-2= | | 9x-62-2x=106 | | 40+2c=600 | | 5p+5-6=6p+3-24 | | 3x+11=57 | | .50x+4=8 |

Equations solver categories